Synthesis, characterization and sorption studies of a zirconium(iv) impregnated highly functionalized mesoporous activated carbons. Issue 23 (6th April 2020) - Sonal, Sonalika; Prakash, Prem; Mishra, Brijesh Kumar; Nayak, G. C.
Abstract : The present work focuses to develop a varied meso-microporous sorbent by using Zr(iv ) as an impregnated metal. The modification develops the oxidative functionalities and porosity of the sorbent that enhances its efficiency for the removal of RB19. Abstract : This study aimed to develop a highly functionalized adsorbent material for the removal of persistent anionic reactive dye. The modification process was commenced via a wet oxidation method by using zirconium salt as an impregnating material. The process led to an increase in the overall porosity, thermal stability and its oxidative functionality. The newly synthesised material was named ZrAC. The morphological and textural images revealed the irregular and eroded structures with an increase in porosity of the modified adsorbent. The results of chemical and spectral analysis disclosed that the material had successfully gained the oxidative functionality over the surface that will favour the removal of anionic dye. Equilibrium isotherms and adsorption kinetics studies insinuate that the overall process of adsorption follows the Sips isotherm and pseudo-second order kinetic model, respectively. The monolayer adsorption capacity of ZrAC was found to be superior (506 mg g −1 ) to AC at 500 mg L −1 concentration of persistent reactive dye. Moreover, the desorption capabilities of ZrAC were found to be more prominent, which finally affirms its potential use in a continuous flow system as a reusable adsorbent. Additionally, the stability of zirconium, corroborated from ICP-MS and XPS data, revealed the stability of zirconium after adsorption cycles thus verified its reusability. Thus, the characterization and experimental results of ZrAC strongly advocated its potential as a future adsorbent for removal of reactive dyes.